Seaweeds of India The Diversity and Distribution of Seaweeds of Gujarat Coast - Jha, Bhavanath; Reddy, C.R.K; Thakur, Mukund C.; Rao, M. Umamaheswara (Developments in Applied Phycology,, 2009)
This book is first of its kind from India and describes a total of 198 species of marine macroalgae representing all three major groups of Chlorophyta, Phaeophyta and Rhodophyta collected from the Gujarat coast which is well known for its algal abundance and diversity. All species described in this book are based on primary collections exclusively made for this purpose and truly reflect the current status of seaweed biodiversity of Gujarat coast. For easy identification, high resolution colour pictures of each species in its natural habitat together with well spread habit of thallus with cross sections showing characteristic features of respective specimens have been provided. Further, the taxonomical descriptions along with distribution and GPS data, abundance, ecology, economic importance etc. have also been included. The contents of this book are user friendly and provide most reliable baseline data on seaweed biodiversity for monitoring and evaluating the impact of any coastal developmental activities aimed at long term economic gains or environmental changes as a result of global warming and climate change. This book will serve as an authentic field guide and reference material for students, teachers, researchers and policy planners interested in algal resource management, utilization and conservation. .